Kualitas Laporan Keuangan Pemerintah Daerah - Garini, Made Putri Ardia; Erawati, Ni Made Adi (E-Jurnal Akuntansi; Vol 32 No 11 (2022), 2022)
This research aims to analyze the factors that affect the quality of the financial statements of the Bangli Regency Government. Data was collected by distributing questionnaires to 25 OPD within the Bangli Regency Government. The method of determining the sample used is purposive sampling, so that 75 people are obtained as samples in this study. The researchers chose multiple linear regression analysis as a technique for analyzing and testing hypotheses. The analysis findings in this research found that human resource competence, government internal control system, organizational commitment, utilization of information technology, and the application of accrual-based government accounting standards have a positive effect on the quality of the Bangli Regency Government's financial reports. Keywords: Human Resources Competence, Internal Control System, Organizational Commitment, Information Technology, Accrual-Based Government Accounting Standards